PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF DEVELOPING CREATIVE QUALITIES OF STUDENTS OF MILITARY EDUCATION FACULTIES - Nodirjon Azamatovich Jalilov; Umidjon Fazilov (Journals Park Publishing, 2022)
In the Armed Forces of our country, as in all fields, special attention is paid to the process of military education, which is considered one of the main factors in the development and implementation of reforms. Reforms and a number of positive changes in the field of military education, further improvement of the pace of development of the effectiveness of military education and effective use of the created opportunities and conditions will expand the pedagogical possibilities of training competitive military education teachers for educational institutions.